MutS HOMOLOG1-Derived Epigenetic Breeding Potential in Tomato. Issue 1 (3rd March 2015) - Yang, Xiaodong; Kundariya, Hardik; Xu, Ying-Zhi; Sandhu, Ajay; Yu, Jiantao; Hutton, Samuel F.; Zhang, Mingfang; Mackenzie, Sally A.
Abstract : Silencing of a mutator gene homolog permits the alteration of plant growth behavior and the enhancement of growth potential using a novel plant breeding strategy. Abstract: Evidence is compelling in support of a naturally occurring epigenetic influence on phenotype expression in land plants, although discerning the epigenetic contribution is difficult. Agriculturally important attributes like heterosis, inbreeding depression, phenotypic plasticity, and environmental stress response are thought to have significant epigenetic components, but unequivocal demonstration of this is often infeasible. Here, we investigate gene silencing of a single nuclear gene, MutS HOMOLOG1 ( MSH1 ), in the tomato ( Solanum lycopersicum ) 'Rutgers' to effect developmental reprogramming of the plant. The condition is heritable in subsequent generations independent of the MSH1-RNA interference transgene. Crossing these transgene-null, developmentally altered plants to the isogenic cv Rutgers wild type results in progeny lines that show enhanced, heritable growth vigor under both greenhouse and field conditions. This boosted vigor appears to be graft transmissible and is partially reversed by treatment with the methylation inhibitor 5-azacytidine, implying the influence of mobile, epigenetic factors and DNA methylation changes. These data provide compelling evidence for the feasibility of epigenetic breeding in a crop plant.